Carbon‐Supported Divacancy‐Anchored Platinum Single‐Atom Electrocatalysts with Superhigh Pt Utilization for the Oxygen Reduction Reaction. Issue 4 (20th December 2018) - Liu, Jing; Jiao, Menggai; Mei, Bingbao; Tong, Yuxin; Li, Yuping; Ruan, Mingbo; Song, Ping; Sun, Gongquan; Jiang, Luhua; Wang, Ying; Jiang, Zheng; Gu, Lin; et al.
Abstract: Maximizing the platinum utilization in electrocatalysts toward oxygen reduction reaction (ORR) is very desirable for large‐scale sustainable application of Pt in energy systems. A cost‐effective carbon‐supported carbon‐defect‐anchored platinum single‐atom electrocatalysts (Pt1 /C) with remarkable ORR performance is reported. An acidic H2 /O2 single cell with Pt1 /C as cathode delivers a maximum power density of 520 mW cm −2 at 80 °C, corresponding to a superhigh platinum utilization of 0.09 gPt  kW −1 . Further physical characterization and density functional theory computations reveal that single Pt atoms anchored stably by four carbon atoms in carbon divacancies (Pt‐C4 ) are the main active centers for the observed high ORR performance. Abstract : Pt single atoms anchored by four carbon atoms neighboring carbon divacancies (Pt‐C4 sites) show high ORR performance. An acidic H2 /O2 single cell with Pt/C as the cathode delivers a maximum power density of 520 mW cm −2 at 80 °C, corresponding to a superhigh platinum utilization of 0.09 gPt  kW −1 .